2019
DOI: 10.1038/s41467-019-13325-9
|View full text |Cite
|
Sign up to set email alerts
|

Carrier multiplication in van der Waals layered transition metal dichalcogenides

Abstract: Carrier multiplication (CM) is a process in which high-energy free carriers relax by generation of additional electron-hole pairs rather than by heat dissipation. CM is promising disruptive improvements in photovoltaic energy conversion and light detection technologies. Current state-of-the-art nanomaterials including quantum dots and carbon nanotubes have demonstrated CM, but are not satisfactory owing to high-energy-loss and inherent difficulties with carrier extraction. Here, we report CM in van der Waals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
71
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(88 citation statements)
references
References 48 publications
(83 reference statements)
16
71
1
Order By: Relevance
“…We attribute this fast decay to ultrafast carrier trapping at defects (see the extended discussion in SI ) in line with previous studies. 21 , 36 While the passivation of these defects will be required for device applications, it does not affect the CM process in this study as CM occurs on a subpicosecond time scale. 21 In Figure 2 c, we present the photoconductivities normalized to the absorbed photon density.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We attribute this fast decay to ultrafast carrier trapping at defects (see the extended discussion in SI ) in line with previous studies. 21 , 36 While the passivation of these defects will be required for device applications, it does not affect the CM process in this study as CM occurs on a subpicosecond time scale. 21 In Figure 2 c, we present the photoconductivities normalized to the absorbed photon density.…”
Section: Resultsmentioning
confidence: 99%
“… 20 Furthermore, Kim and colleagues extended recently such studies into multilayered van der Waals (vdW) materials of MoTe 2 and WSe 2 . 21 They reported near-perfect MEG in vdW structures employing transient absorption (TA) spectroscopy, that is, a unity quantum yield with an onset energy of 2 E g . However, the mechanism on which the CM/MEG takes place in vdW materials remains elusive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 ] A similar rapid charge transfer was observed in a layered MoTe 2 thin film with an ideal 2 E g . [ 21 ] Another merit of this technique is the high spatial resolution of the photocurrent measurement by near‐field detection that is helpful in investigating the CM in one QD or multiple QDs at the very apex of the Au tips.…”
Section: Figurementioning
confidence: 99%
“… 14 Recently, CM with onset and efficiency similar to the low band gap perovskites of the present study has been reported for MoTe 2 and WSe 2 (see Figure S6 for comparison), although the explanation in these materials remains elusive. 30 In Pb-chalcogenides, the excess energy above the band gap is equally distributed between electron and hole, which sets the CM threshold at three times the band gap. If the photon energy in excess of the band gap is taken up completely by one of the charge carriers and utilized for CM then, ideally, the QY can reach 2 at exactly twice the band gap.…”
mentioning
confidence: 99%